2014
DOI: 10.1111/1469-0691.12605
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after nucleos(t)ide analogue discontinuation in HBeAg-positive chronic hepatitis B patients

Abstract: Nucleos(t)ide analogue (NUC) resistance is an important clinical risk resulting from long-term therapy in chronic hepatitis B (CHB) management. Discontinuation of NUCs is a feasible strategy to reduce resistance. We aimed to observe the outcomes after NUC withdrawal in HBeAg-positive CHB patients. A total of 97 patients (11 patients with HBsAg loss and 86 patients with sustained HBeAg seroconversion) were enrolled. HBV DNA levels and alanine aminotransferase (ALT) levels were monitored regularly after disconti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…The literature search initially identified 972 papers; of those, 25 fulfilled the inclusion and exclusion criteria for this review (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo). The main characteristics of the included studies and patients are presented in Tables and .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search initially identified 972 papers; of those, 25 fulfilled the inclusion and exclusion criteria for this review (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo). The main characteristics of the included studies and patients are presented in Tables and .…”
Section: Methodsmentioning
confidence: 99%
“…In total, 2332 (each study contribution from 11 to 401) patients were included in the 25 studies. All but one were cohort studies (three prospective, one retrospective‐prospective, and 20 retrospective, while one was a randomized study comparing the effects of 12 versus 24 months of additional therapy after response to lamivudine in HBeAg‐negative CHB . One study was found to have high quality, 14 to have acceptable quality, and 10 to have low quality based on their risk of bias assessments (http://onlinelibrary.wiley.com/doi/10.1002/hep.28438/suppinfo).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations